Citra Pemimpin Daerah di Media Sosial: Analisis Isi Tweet Mengenai Sutiaji di Twitter - Sekar Arum Nuswantari (Unitri Press, 2022)
This research looks at the discussion of regional leaders from the point of view of political imagery on Twitter. Twitter is one of the media used in political communication, whether for political campaigns or public discussions. This study intends to describe three things. First, to explain how the trend of opinion regarding Sutiaji's image as mayor on Twitter. Second, describe how Sutiaji's image on Twitter is based on image aspects. Third, look at the type of user account that talks about Sutiaji. Researchers analyzed tweets using qualitative content analysis methods, which were collected from June 10, 2022 to June 16, 2022. After tweets were collected, the analysis was carried out using opinion tendencies (positive, neutral, and negative) and image aspects, namely competence, leadership, integrity, and personal characteristics. As a result, Sutiaji's image tends to be neutral in discussions on Twitter. When viewed from the type of account, more negative discussions are uploaded by personal accounts. Many positive discussions came from media and government accounts. Many discussions about aspects of personal characteristics, leadership and competence. Abstrak Penelitian ini melihat pembahasan mengenai pemimpin daerah dari sudut pandang citra politik di Twitter. Twitter merupakan salah satu media yang digunakan dalam komunikasi politik, baik untuk kampanye politik, ataupun diskusi publik. Penelitian ini bermaksud mendeskripsikan tiga hal. Pertama, menjelaskan bagaimana kecenderungan opini mengenai citra Sutiaji sebagai walikota di Twitter. Kedua, mendeskripsikan bagaimana citra Sutiaji di Twitter berdasarkan aspek-aspek citra. Ketiga, melihat jenis akun pengguna yang membahas tentang Sutiaji. Peneliti menganalisis tweet menggunakan metode analisis isi kualitatif. Setelah tweet terkumpul, analisis dilakukan menggunakan kecenderungan opini (positif, netral, dan negatif) dan aspek-aspek citra yaitu kompetensi, kepemimpinan, integritas, dan karakteristik personal. Hasilnya, citra Sutiaji cenderung netral dalam pembahasan di Twitter. Jika dilihat dari jenis akun, pembahasan negatif lebih banyak diunggah oleh akun personal. Pembahasan positif banyak berasal dari akun media dan pemerintah. Pembahasan banyak mengenai apek karakteristik personal, kepemimpinan dan kompetensi.